Dermatoglyphes digitaux et palmaires d'une communauté rurale canadienne - française - Benoist, Jean (Anthropologica, 2022)
This article presents the analysis of the finger prints of nearly half of the available population of a parish in the "Cantons de l'Est" of the province of Quebec. Some small variations in the data from samples taken in Montreal or in Europe could indicate regional tendencies. The collection of similar data in Quebec would give more precisions as to the extension of the variations.